DIPLOMASI PEMERINTAH INDONESIA KEPADA ARAB SAUDI TENTANG PENAMBAHAN KUOTA HAJI INDONESIA - Faundra, Annas; Halifa Haqqi, Christy Damayanti, (Solidaritas, 2017)
DIPLOMASI PEMERINTAH INDONESIA KEPADA ARAB SAUDI TENTANG PENAMBAHAN KUOTA HAJI INDONESIAÂ Annas Faundra, Dra. Christy Damayanti, M.Si., Halifa Haqqi, S.IP., MA.13430017Ilmu Hubungan InternasionalFakultas Ilmu Sosial Dan Ilmu PolitikUniversitas Slamet Riyadi SurakartaÂ ABSTRACTIndonesian bilateral diplomacy with Saudi Arabian reinforces bilateral communication or establish Government to Government negotiation with Saudi Arabian and involves not only Government to Government but also Non-government, Hajj travel agent, in which hajj quota reduction in 2013 was also brought into Multilateral discussion in OKI forum. The theories employed by author were diplomacy, Government to Government, and negotiation approaches. The author employed a descriptive qualitative approach; the data employed consisted of primary and secondary data from a variety of sources related to Indonesia Government Diplomacy to Saudi Arabian about the increase of Indonesian Hajj quota. The method of collecting data used was interview and document study. From the result of research, it could be concluded that Indonesia conducted diplomacy with Saudi Arabian using bilateral diplomacy including Government to Government Negotiation, non-government negotiation with Hajj travel agent, and multilaterally in OKI forum.Keywords: Bilateral Diplomacy, Multilateral Diplomacy, Negotiation, Hajj Quota